Vampire diaries : the return, nightfall - Smith, Lisa Jane, 1965- (Hachette Children's Group, 2010)
A phenomenally popular vampire romance sequence - now showing on ITV2 - from the best selling author of Night World, L. J. Smith. Elena Gilbert is alive - again! When Elena sacrificed herself to save the two vampire brothers who love her she was consigned to a fate beyond death. Until a powerful supernatural force pulled her back. Now Elena is not just human. She has powers. What's more, her blood pulses with a unique force that makes her irresistible to any vampire. Both brothers still want Elena to be theirs, but something bigger and more powerful than all of them may want her more...